Cover Image. Issue 2 (9th April 2021) - Unknown
Abstract : The cover image from Hideko T Oyama and colleagues shows polarized optical micrographs of spherulites in neat PPS (left color image in reddish yellow and blue) and (95/5)PPS/PVP blend (right color image with small PVP black domains in light yellow and green) observed at the same magnification. Upon blending, the spherulite size significantly increases, and the interference color differs due to a change in the birefringence of the spherulites. In the article e10165, it is indicated that the former change brought about a decrease in the crystallization rate and melt crystallization temperature, while the latter change is attributed to an increased ordering of fibrils in spherulites. (doi.org/10.1002/pcr2.10165 ) Abstract : The cover image from Hideko T Oyama and colleagues shows polarized optical micrographs of spherulites in neat PPS (left color image in reddish yellow and blue) and (95/5)PPS/PVP blend (right color image with small PVP black domains in light yellow and green) observed at the same magnification. Upon blending, the spherulite size significantly increases, and the interference color differs due to a change in the birefringence of the spherulites. In the article e10165, it is indicated that the former change brought about a decrease in the crystallization rate and melt crystallization temperature, while the latter change is attributed to an increased ordering of fibrils in spherulites. (doi.org/10.1002/pcr2.10165 )